ChemInform Abstract: Direct and Facile Synthesis of Acyl Isothiocyanates from Carboxylic Acids Using Trichloroisocyanuric Acid/Triphenylphosphine System. Issue 19 (May 2015) - Entezari, Najmeh; Akhlaghinia, Batool; Rouhi‐Saadabad, Hamed
Abstract: The excellent yields, short reaction times, and mild reaction conditions make this procedure an useful and attractive alternative to the currently available methods.